(untitled) (Journal of Health Sciences, 2014)
Introduction: Despite recent advances in anesthesia, cardiopulmonary bypass and surgical techniques, children undergoing congenital heart surgery require postoperativemechanical ventilation. Early extubation was definedas ventilation shorter than 12 hours. Aim of this study is to identify factors associated with successful early extubation after pediatric cardiac surgery.Methods: The study was performed during period from January 2006 to January 2011 at Pediatric Clinic and Heart Center University Clinical center Sarajevo. One hundred children up to 5 years of age, who have had congenital heart disease, with left–right shunt and obstructive heart disease were included in the study. Patients were divided into two groups: Group I - patients extubated within 12 hours after surgery and Group II - patients extubated 12 or more hours after surgery. Results: The most frequently encountered preoperative variables were age with odds ratio 4% 95%CI (1-7%), Down's syndrome 8.5 95%CI (1.6-43.15), failure to thrive 4.3 95%CI( 1-18). Statistically significant postoperative data included lung disease (reactive airways, pneumonia, atelectasis, pneumothorax) and with odds ratio 35.1 95 %CI (4-286) and blood transfusion with odds ratio 4.6 95%CI (2-12). Blood transfusion (p=0.002) (Wald=9.2) 95%CI (2-12), during as well as after operation procedure has statistically significant influence on prediction time of extubation. Proven markers were age with cut of 21.5 months (sensitivity 74% and specificity 70%) and extracorporeal circulation (ECC) with cut-of 45.5 minutes (sensitivity 71% and specificity 65%).Conclusion: Early extubation is possible in many children undergoing congenital heart surgery. Younger age and prolonged ECC time are markers associated with prolonged mechanical ventilation.